2009
DOI: 10.1021/ac901096h
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity of Pd−Co Bimetallic Mixtures for Formic Acid Oxidation Studied by Scanning Electrochemical Microscopy

Abstract: The electrochemical oxidation of formic acid was studied by the tip generation-substrate collection (TG-SC) mode of scanning electrochemical microscopy (SECM), extending the number of applications of SECM in electrocatalysis. Formic acid was generated at a Hg on Au ultramicroelectrode (UME) tip by reduction of CO(2) in a 0.1 M KHCO(3) solution saturated with this gas. The electrocatalytic activity of different Pd-Co bimetallic compositions was evaluated using a Pd-Co electrocatalyst array formed by spots depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 32 publications
(42 reference statements)
0
39
0
Order By: Relevance
“…It was reported that the catalytic activity and stability of Pd were increased by addition of another precious metal into the catalyst, such as Au [22], Pt [23] or Ir [24]. Non-noble metals such as Pb [25], Sn [22,26], Co [27,28] and boron [29] have also been used as promoters for formic acid catalytic electrooxidation. However, the performances of Pd catalysts need further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the catalytic activity and stability of Pd were increased by addition of another precious metal into the catalyst, such as Au [22], Pt [23] or Ir [24]. Non-noble metals such as Pb [25], Sn [22,26], Co [27,28] and boron [29] have also been used as promoters for formic acid catalytic electrooxidation. However, the performances of Pd catalysts need further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, new electroanalytical techniques have been recently introduced to improve this screening step. In particular, the scanning electrochemical microscopy (SECM) [34,35] has demonstrated its utility as a rapid and high throughput technique in screening electrocatalyts [36] for processes A c c e p t e d M a n u s c r i p t 5 such as the oxygen reduction reaction (ORR) [37][38][39][40][41][42], methanol interference during ORR [43], chlorine evolution [44] and oxygen evolution reactions (OER) [45,46], formic acid oxidation (FAOR) [47,48] and methanol oxidation reactions (MOR) [48].…”
Section: Page 4 Of 40mentioning
confidence: 99%
“…Both the feedback mode [4] and generation/collection modes [5,6] offer significant advantages for the quantitative detection of reaction intermediates and measurements of the electrontransfer kinetics. Electrocatalyst screening techniques based on SECM show incomparable versatility in the comparison and selection of electrocatalysts and photoelectrocatalysts [5,[7][8][9][10]. In order to probe more catalytic spots during a screening experiment, the distance between spots should be controlled as small as possible.…”
Section: Introductionmentioning
confidence: 99%